2016
DOI: 10.1038/srep28858
|View full text |Cite
|
Sign up to set email alerts
|

3,6-dihydroxyflavone suppresses the epithelial-mesenchymal transition in breast cancer cells by inhibiting the Notch signaling pathway

Abstract: The epithelial to mesenchymal transition (EMT) is a critical developmental program in cancer stem cell (CSC) maintenance and in cancer metastasis. Here, our study found that 3,6-DHF could effectively inhibit EMT in BC cells in vitro and in vivo. 3,6-DHF effectively inhibits the formation and proliferation of BCSCs, and consequently reduces the tumor-initiating capacity of tumor cells in NOD/SCID mice. Optical in vivo imaging of cancer metastasis showed that 3,6-DHF administration suppresses the lung metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…67,185,186 3,6-Dihydroxyflavone is ubiquitous in vegetables and fruits and blocks EMT in breast cancer cells through suppressing the Notch signaling pathway. 47 Moreover, luteolin inhibited EMT in gastric cancer by the Notch signaling pathway. 38 In addition, emodin is a main bioactive component of Polygonum cuspidatum that suppressed EMT in alveolar epithelial cells via the Notch signaling pathway.…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…67,185,186 3,6-Dihydroxyflavone is ubiquitous in vegetables and fruits and blocks EMT in breast cancer cells through suppressing the Notch signaling pathway. 47 Moreover, luteolin inhibited EMT in gastric cancer by the Notch signaling pathway. 38 In addition, emodin is a main bioactive component of Polygonum cuspidatum that suppressed EMT in alveolar epithelial cells via the Notch signaling pathway.…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…Another γ‐secretase inhibitor, RO4929097, not only inhibited EMT, invasion, and metastasis in cervical cancer HeLa and CaSki cells but also exerted significant therapeutic effects in patients with recurrent malignant glioma, cervical and colon cancer and advanced solid tumors in clinical trials . 3,6‐Dihydroxyflavone is ubiquitous in vegetables and fruits and blocks EMT in breast cancer cells through suppressing the Notch signaling pathway . Moreover, luteolin inhibited EMT in gastric cancer by the Notch signaling pathway .…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…Notch signaling is activated by NICD, followed by the NICD cleavage products translocating to the nucleus and activating the expression of the primary Notch target gene Hes-1 [19,20]. In order to explore whether the Notch signaling pathway participated in the effect of siCLDN-1 on the regulation of migration and EMT, we determined the effects of siCLDN-1 on NICD and Hes-1 expression.…”
Section: Mechanisms Of Sicldn-1 In Regulation Of Migration and Emtmentioning
confidence: 99%
“…As a result, tumor invasion, migration, and stem cell formation were inhibited. Further studies showed that Notch1 inhibition and miR-34a upregulation were involved 116. Nevertheless, in tamoxifen-resistant MCF-7TR breast cancer cells, resveratrol reversed EMT by reducing endogenous TGF-β and inhibiting SMAD phosphorylation 117…”
Section: Effects Of Several Common Natural Products On Tumor Emtmentioning
confidence: 99%